PENGARUH GAYA KEPEMIMPINAN, KOMUNIKASI ORGANISASI, DAN PENGEMBANGAN SUMBER DAYA MANUSIA TERHADAP PRESTASI KERJA PADA BADAN PENELITIAN DAN PENGEMBANGAN DAERAH KABUPATEN PANGKEP - ERNAWATI NURSAID; Maryadi Maryadi; Saripuddin D (Jurnal Aplikasi Manajemen & Kewirausahaan MASSARO, 2021)
This study aims to determine and analyze the influence of leadership style, organizational communication and human resource development partially and simultaneously on employee work performance at the Regional Research and Development Agency of Pangkep Regency, as well as the most dominant variable influencing employee work performance at the Regional Research and Development Agency. Pangkep Regency. The research was conducted at the Regional Research and Development Agency of Pangkep Regency. The research time was November to December 2019 by taking 43 employees as the research sample. The results of this study prove that partially it is proven that leadership style and organizational communication have an effect on work performance, while human resource development is proven to have no effect on work performance. This study also proves that simultaneously leadership style, organizational communication and human resource development affect work performance in the regional research and development agency of Pangkep Regency.This research produces a determination coefficient value of 98.8% which indicates that this research model can explain student decisions. influenced by 77.2% of this research variable and 22.8% influenced by other variables not examined in this study. From the analysis of the three independent / independent variables (leadership style, organizational communication and human resource development), it is found that leadership style (X1) is the most dominant factor influencing the work performance of the employees of the Regional Research and Development Agency of Pangkep Regency.